Ocular manifestations in HIV/AIDS cases in Nepal - Lamichhane, G; Shah, DN; Sharma, S; Chaudhary, M (Nepalese Journal of Ophthalmology, 2010)
Background: A significant number of patients with HIV/AIDS can have ocular manifestations. Almost every structure in the eyes can be affected in this condition. Objective: To study various ocular manifestations in the cases known to be infected with HIV. Materials and methods: A cross-sectional descriptive study was carried out including 117 subjects positive for HIV using the purposive sampling method. Their demographic pattern and ocular findings were studied. Findings were recorded in the pro forma developed for the study. Statistics: SPSS ver 14.0 was used for data analysis. The p value of <0.05 was considered as significant. Results: A total of 117 HIV infected cases were included in this study. Among them, 76 (64.95 %) were male and 41 (35.05 %) female. The mean age of the subjects was 30.04 ± 11.32 years. The duration of HIV detection ranged from 1-5 years. Ocular complaints were present in 26.49 % of the subjects. Ocular manifestations were present in 56 % of the patients with complaints and in 27.3 % of asymptomatic patients. Ocular involvement was seen in 55 (47 %) patients. The common anterior segment findings were herpes zoster ophthalmicus (4.27 %), anterior uveitis (2.56 %), blepharitis (2.56 %) and conjunctivitis (1.7 %), whereas HIV retinopathy (19.6 %), CMV retinitis (5.1 %), ocular toxoplasmosis (2.5 %) and presumed ocular tuberculosis (0.85 %) were common posterior segment findings. Conclusion: Herpes zoster ophthalmicus, anterior uveitis, HIV retinopathy and CMV retinitis are common ocular manifestations associated with HIV infections. Keywords: HIV/AIDS; anterior and posterior segments; ocular involvement DOI: 10.3126/nepjoph.v2i1.3704 Nep J Oph 2010;2(1) 45-50